Exopolysaccharides Synthesized by Rhizospheric Bacteria: A Review Focused on Their Roles in Protecting Plants against Stress - Carezzano, Maria Evangelina (2023)
Plants are constantly exposed to a wide range of environmental factors that cause different kinds of stress, such as drought, salinity, heat, frost, and low nutrient availability. There are also biotic sources of stress, which include pathogens (bacteria, viruses, pests), herbivores, and plant competitors. These various types of stress affect normal plant physiology and development, and may lead to significantly lower yields. However, certain microorganisms (MOs), known as plant growth-promoting rhizobacteria (PGPR), can interact with and benefit plants in stressful environments. They do so through a series of mechanisms which contribute to minimizing the negative effects of plants? responses to stress. This review summarizes current knowledge about those mechanisms, with a focus on the production of exopolysaccharides (EPSs). These compounds can act as osmoprotectants, promote the production of phytohormones, prevent the entry of pathogens through roots, bioremediate metals, and improve soil structure and permeability, among many other beneficial effects. This makes them suitable alternatives to guarantee food security while reducing the excessive use of chemical agricultural inputs and their harmful consequences for the environment.